Neonatal Orthoptic Screening Battery (NOSB): Four-decade Experience of Orthoptic Best Practice - Flora, Mondelli; Rita, Barone; Andrea, Buscemi; Marinella, Coco (International Journal of Pediatrics and Child Health, 2024)
The present study describes the neonatal orthoptic screening battery (NOSB), a comprehensive orthoptic screening, based on four decades of application, aimed at early identification of signs and symptoms of ocular pathology or functional disorders. The NOSB allows for verifying the integrity of ocular components and early detection of functional alterations in ocular movements that could lead to the development of amblyopia or strabismus. The NOSB is the result of 45 years of screening activity in a primary health center assured by the National Health System in the city of Ragusa – Italy. It aims to examine and assess the neonate within the first 3 days of extrauterine life to identify visual system issues as early as possible. The NOSB may be conducted by Orthoptists, healthcare professionals specializing in neonatal and pediatric visual prevention. The Neonatal Orthoptic Screening battery (NOSB) here reported is proposed as a standard suitable for widespread adoption to be considered a "Best Practice".